The Taming of the shrew - Shakespeare, William (Sweet Cherry Publishing UK, 2013)
SLY. I'll pheeze you, in faith. HOSTESS. A pair of stocks, you rogue! SLY. Y'are a baggage; the Slys are no rogues. Look in the chronicles: we came in with Richard Conqueror. Therefore, paucas pallabris; let the world slide. Sessa! HOSTESS. You will not pay for the glasses you have burst? SLY. No, not a denier. Go by, Saint Jeronimy, go to thy cold bed and warm thee.